Hemoglobin, Hematocrit, Leukocyte, and Platelet Changes Due To Ultrafiltrationhemodialysis in Chronic Kidney Disease Patients - Nathalya Dwi Kartikasari; Paulus Budiono Notopuro; Widodo Widodo; Yetti Hernaningsih (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2020)
Managing anemia in Chronic Kidney Disease (CKD) patients with hemodialysis (HD) is a challenge to physicians. The present consensus does not address the proper time of blood sampling in HD patients, but higher ultrafiltration (UF) volume (a process of removing fluid excess during HD) may alter hematologic parameters. The objective of this study was to compare some parameters of the Complete Blood Count (CBC); hemoglobin (Hb), hematocrit (Hct), leukocyte (WBC), and platelet counts (Plt) before and after HD. This method was a cross-sectional study performed in the HD Unit, Dr.Soetomo Hospital, including 51 CKD patients selected consecutively, divided into two groups based on the UF volume (2 L and >2 L). Complete blood count pre- and post-HD were measured using Sysmex XN 1000. The results were 25 males and 26 females in this study, age ranged from 20 to 74-year-old, and 36 patients with UF volume >2 L. Only HD with UF >2 L showed significant increases for Hb (9.35g/dL to 10.00 g/dL), Hct (29.80% to 31.15 %), and Plt (209.00x103/µL to 213.00x103/µL) but WBC did not change significantly. These changes were believed to be caused by ultrafiltration. The conclusion was Hb, Hct, and Plt increased significantly with UF â‰¥2 L in HD CKD patients.